(untitled) (American Journal of Islam and Society, 2014)
By and large, contemporary Muslims enjoy all the facilities and comforts of modern life. However, in relation to a governing legal system, they still wish to live according to the laws promulgated through the Qur’an and Sunnah (the Shari‘ah) without any alteration and addition. Yet such an approach does not provide a solution for all existing and emerging offences. An acceptable solution is possible if, as proposed by Muhammad Iqbal, the great philosopher of the East, we reinterpret Islam’s foundational legal principles in light of our own experiences and conditions. I hold that the foundational legal principles regarding crime and punishment are ḥadd(a fixed punishment mandated by the Qur’an and Sunnah), qiṣāṣ(equal retaliation [an eye for an eye]), dīyah(blood money, ransom), and ta‘zīr(punishment, usually corporal).